Associations Between Morning Salivary and Blood Cortisol Concentrations in Individuals With Obstructive Sleep Apnea Syndrome: A Meta-Analysis - Imani, Mohammad Moslem; Sadeghi, Masoud; Khazaie, Habibolah; Sanjabi, Arezoo; Brand, Serge; Brühl, Annette; Sadeghi Bahmani, Dena (Frontiers in Endocrinology, 2021)
Background: Obstructive sleep apnea syndrome (OSAS) may be associated with an increase in hypothalamic-pituitary-adrenocortical axis activity (HPA AA). We reviewed research comparing the morning salivary and blood (serum and plasma) cortisol concentrations of individuals with OSAS to those of healthy controls. Methods: We made a systematic search without any restrictions of the PubMed/Medline, Scopus, Cochrane Library, and Web of Science databases for relevant articles published up to August 25, 2019. Results: Sixteen studies were analyzed in this meta-analysis; five studies compared morning salivary concentrations, five compared serum concentrations, four compared plasma cortisol concentrations, and two compared both salivary and plasma concentrations. In pediatric samples, compared to healthy controls, those with OSAS had significantly lower saliva morning cortisol concentrations (MD = -0.13 µg/dL; 95% CI: 0.21, -0.04; P = 0.003). However, among adults no significant differences were observed for serum cortisol concentrations, plasma cortisol concentrations, or salivary morning cortisol concentrations of OSAS cases when compared to healthy controls. Conclusion: Cortisol concentrations did not differ between adults with OSAS and healthy controls. In contrast, among children morning salivary cortisol concentrations were lower in those with OSAS than in healthy controls. Given that reduced HPA AA is observed among individuals with chronic stress, it is possible that children with OSAS are experiencing chronic psychophysiological stress.